Particulate pollution from motor vehicles in an urban street canyon in Nottingham, UK. (20th February 2004) - Namdeo, Anil; Baker, Christopher; Colls, Jeremy
Examining air quality information is important in understanding possible human exposure and potential impacts in health and welfare. It has recently been realised that smaller-diameter particulate pollutants are implicated in the increasing incidence of asthma and cancer. This paper presents the results of a study on particulate pollution from motor vehicles in urban areas. PM10 and other fractions of airborne particulate matters were measured using two aerosol spectrometers in an urban street canyon in Nottingham, UK. Detailed information on traffic flow and vehicles was collected using video recording and sample surveys. Variations in temporal, spatial and size distributions of PM10 and inhalable, thoracic and alveolic fractions of particulates are presented. This study will be of benefit to researchers in the field of atmospheric dispersion modelling and to epidemiologists looking at the health effects of particulate pollution.